Penggunaan Model Pembelajaran Matematika Realistik pada Mahasiswa - Gregorius Taga; Vivien Restianim (Jurnal Pendidikan Matematika:Judika Education, 2020)
The purpose of this study was to determine student learning outcomes in algebraic subjects in the University of Flores Mathematics Education Study Program using realistic mathematics learning device models. This type of research is quantitative research with quasi-experimental design, pretest and posttest group, the sample is all fourth semester students of mathematics education program FKIP Flores University in 2018/2019 academic year. Data obtained using student learning outcomes, data processed using ANOVA statistical tests. The results obtained by the value of Fcount 77.13 is greater than Ftable 4.10 at dk 37. Calculation of student learning outcomes in the experimental group after using realistic mathematics learning models, seen student learning outcomes increased significantly. Conclusion, learning mathematics using realistic models can be used as an alternative to improving student learning outcomes in algebraic structure subjects. Keywords: Learning Outcomes, Learning Models, Realistic Mathematics, Algebraic Structure